2019
DOI: 10.1177/0361198119851447
|View full text |Cite
|
Sign up to set email alerts
|

Use of Objective Safety Evidence to Deploy Automated Enforcement Resources

Abstract: Automated enforcement programs have been an important tool for improving traffic safety. Previous work provides strong evidence supporting the impact that these programs have on increasing safety either on a micro-level (e.g., road segments), or at a macro-level (e.g., neighborhood, city). In both cases, there are many variables that can influence and affect the safety impacts of the enforcement program. Additionally, there is a lack of understanding of how specific deployment parameters (e.g., how often to vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…While more research has been focused on modeling collision frequencies, recent research has shown that Tobit regression models provide some advantages [30,31]. Instead of using collision counts, this technique considers collision rates which neutralizes the effect of the exposure variable and measures the risk of collision involvement [32][33][34] and was first applied by Anastasopoulos et al [29] in the field of traffic safety. Since then, other studies applied the Tobit model to understanding the influencing factors of collision rates [33,35].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…While more research has been focused on modeling collision frequencies, recent research has shown that Tobit regression models provide some advantages [30,31]. Instead of using collision counts, this technique considers collision rates which neutralizes the effect of the exposure variable and measures the risk of collision involvement [32][33][34] and was first applied by Anastasopoulos et al [29] in the field of traffic safety. Since then, other studies applied the Tobit model to understanding the influencing factors of collision rates [33,35].…”
Section: Methodsmentioning
confidence: 99%
“…Recent research identified that a more robust unit of analysis to address the concerns associated with high-level aggregation (i.e., at a national/city level) as well as the microlevel aggregation (i.e., intersection). Ibrahim and Sayed [5,29] investigated the impact of MAE on collisions at a Traffic Analysis Zone (TAZ) level. The authors found that collision reductions for each TAZ were associated with spending a longer time enforcing a site for each visit in a deployment.…”
Section: Automated Enforcementmentioning
confidence: 99%
See 1 more Smart Citation